Biomechanical evaluation of three implants for treating unstable femoral intertrochanteric fractures: finite element analysis in axial, bending and torsion loads - Bai, HuanAn; Liu, Lu; Duan, Ning; Xue, HanZhong; Sun, Liang; Li, Ming; Li, Zhong; Zhang, Kun; Wang, Qian; Huang, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
How to effectively enhance the mechanical stability of intramedullary implants for unstable femoral intertrochanteric fractures (UFIFs) is challenging. The authors developed a new implant for managing such patients. Our aim was to enhance the whole mechanical stability of internal devices through increasing antirotation and medial support. We expected to reduce stress concentration in implants. Each implant was compared to proximal femoral nail antirotation (PFNA) via finite element method.Methods: Adult AO/OTA 31-A2.3 fracture models were constructed, and then the new intramedullary system (NIS), PFNA, InterTan nail models were assembled. We simulated three different kinds of load cases, including axial, bending, and torsion loads. For further comparison of PFNA and the NIS, finite element analysis (FEA) was repeated for five times under axial loads of 2100 N. Two types of displacement and stress distribution were assessed.Results: Findings showed that the NIS had the best mechanical stability under axial, bending, and torsion load conditions compared to PFNA and InterTan. It could be seen that the NIS displayed the best properties with respect to maximal displacement while PFNA showed the worst properties for the same parameter in axial loads of 2100 N. In terms of maximal stress, also the NIS exhibited the best properties while PFNA showed the worst properties in axial loads of 2100 N. For bending and torsion load cases, it displayed a similar trend with that of axial loads. Moreover, under axial loads of 2100 N, the difference between the PFNA group and the NIS group was statistically significant (p<0.05).The new intramedullary system exhibited more uniform stress distribution and better biomechanical properties compared to the PFNA and InterTan. This might provide a new and efficacious device for managing unstable femoral intertrochanteric fractures.